The moderating effects of gender and tenure on the antecedents of employee engagement in local governments - Md Rami, Ahmad Aizuddin; Roslan Khairi, Erda; Ahrari, Seyedali; Ibrahim, Asmawi; Olaitan, Ahmed Ahmed (Discover, 2025)
Employee engagement is a critical factor in organizational success, particularly in the context of local governments, where effective public service delivery is paramount. Understanding the antecedents of employee engagement is essential for enhancing productivity, job satisfaction, and overall organizational performance. This study aims to identify the factors of organizational structure that contribute to employee engagement among the local government workforce in Malaysia. It is a quantitative study involving a total of 389 employees from 98 local government agencies. The findings indicate that the level of employee engagement, centralized hierarchy, and formalized job codification among the Malaysian local government workforce is high. Furthermore, the results reveal a moderate level of formalized rule observation and centralized decision-making. These findings also suggest a significant relationship between the antecedents and employee engagement. Regression analysis demonstrates that the centralized hierarchy of authority is the most influential factor in employee engagement. Additionally, the results of the moderation analysis show that the relationships between organizational factors and employee engagement are not influenced by gender and tenure in service. In conclusion, this study demonstrates that the employee engagement of the local government workforce in Malaysia is significantly affected by the four factors of organizational structure. These results support the importance of organizational structure, thereby contributing to the current literature on the effectiveness of local governments in Malaysia.